Toward a radical behaviorist social psychology from Celso Pereira de Sá - Roberta Garcia Alves; Rodrigo Lopes Miranda (Estudos de Psicologia (Campinas))
Abstract Objective This article aims to revisit and analyze the proposal of a Radical Behaviorist Social Psychology based on the work of Celso Pereira de Sá between 1970 and 1990. Method The author’s work was examined using the Iramuteq software and analyzed through a partial adoption of the Contextual Text Interpretation Procedure. Results The results are discussed based on indicators of textual relevance, along with excerpts representative of the theoretical foundations constructed by the author. The author reflects on the role of the intellectual and the production of scientific knowledge in addressing distinct Brazilian social problems. Sá emphasized the anti-intellectualist role of popular political education, envisioning a scenario where the population possesses the capacity to generate knowledge about its reality and intervene in it. Conclusion The author proposed a Radical Behaviorist-based Social Psychology, emphasizing the necessity for constant interdisciplinary dialogues with other authors and disciplines within the Social Sciences.